2021
DOI: 10.47722/imrj.2001.04
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Support Policy of Nepal: Cases of Subsidies

Abstract: As an agrarian nation, agriculture policies of Nepal have been prioritized subsidies to increase production, improve food security, and reduce poverty. Nepal government has been allocating a huge amount each year for agricultural subsidies. This paper focuses on identifying the critical issues of the effective implementation of agricultural policies and programs in Nepal. The paper is based on primary and secondary sources of information. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…According to the participants' perspectives, ineffective governance signs such as confusion in decision-making and shortcomings in governance processes, institutions, and practises led to a lack of transparency, accountability, responsibility, and responsiveness, which ultimately resulted in a lack of effective implementation of the policy. This is in line with the study, which stated that lack of good governance, lack of transparency, corruption, and degradation of values and ethics, including financial morality (nepotism and favouritism), as fake farmers supported by political leaders and commissioned by government officials, are critical issues for the effective implementation of agricultural policies and programs in Nepal (Mahesh, 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to the participants' perspectives, ineffective governance signs such as confusion in decision-making and shortcomings in governance processes, institutions, and practises led to a lack of transparency, accountability, responsibility, and responsiveness, which ultimately resulted in a lack of effective implementation of the policy. This is in line with the study, which stated that lack of good governance, lack of transparency, corruption, and degradation of values and ethics, including financial morality (nepotism and favouritism), as fake farmers supported by political leaders and commissioned by government officials, are critical issues for the effective implementation of agricultural policies and programs in Nepal (Mahesh, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…Findings of this study about barriers to policy implementation range from mismanagement, including ineffective administrative measures, ineffective planning, technical risks, and ineffective policy instruments, to economic difficulties, including financial difficulties and high production costs, along with ineffective governance and foreign constraints. These findings complement earlier literature that highlights policy implementation as being hindered by a number of factors, among them limited institutional capacity and a lack of cooperation among different sectors Ambali & Murana, 2017;Tesfagabir (2017); Ville et al (2017); Letswa (2018); Dezhman & Daneshfard (2021), a lack of sufficient funding and production inputs (Resnick et al, 2018;Munene, 2020;Schiller et al, 2020), limited agricultural technical know-how, weak agricultural research and weak extension services (Kamarulzaman, 2017;Bamoi & Yilmaz, 2021) , and a lack of good governance (Mahesh, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, rural farmers with low levels of education do not have enough knowledge of the coping strategies for the adverse impacts of climate change on the agricultural system [36]. The subsidies and grants provided by the government were highly influenced by political power and people, so political influence must be discouraged in order to implement grants and subsidies specifically for needy farmers in Nepal [80] as well as in India [16]. The subsidy program of the Nepal government is limited to wheat and paddy and needs to be expanded to include pulses and oilseed crops [81].…”
Section: Suggestions and Recommendationsmentioning
confidence: 99%
“…There are many moral hazards of subsidy abuse. Shrestha (2021) concluded that agricultural subsidies supported by different organizations have not been utilized properly and smallholders have not benefited from these supports. Even the distribution of the subsidies was heavily influenced by political power.…”
Section: Almost All Projects Shown Inmentioning
confidence: 99%